2006
DOI: 10.1038/sj.emboj.7601218
|View full text |Cite
|
Sign up to set email alerts
|

Human SMC5/6 complex promotes sister chromatid homologous recombination by recruiting the SMC1/3 cohesin complex to double-strand breaks

Abstract: The structural maintenance of chromosomes (SMC) family of proteins has been implicated in the repair of DNA double-strand breaks (DSBs) by homologous recombination (HR). The SMC1/3 cohesin complex is thought to promote HR by maintaining the close proximity of sister chromatids at DSBs. The SMC5/6 complex is also required for DNA repair, but the mechanism by which it accomplishes this is unclear. Here, we show that RNAi-mediated knockdown of the SMC5/6 complex components in human cells increases the efficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
266
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(293 citation statements)
references
References 54 publications
24
266
3
Order By: Relevance
“…For example, the cohesion defect impairs sister chromatid recombination [31,66], increasing intra-chromatid recombination in the tandem array of ribosomal repeats [36]. Recent work even suggested that Smc5-Smc6 would be required for the efficient loading of cohesin to DSB sites [67,68]. Smc5-Smc6 could restrain the initiation of strand invasions between different chromosomes that lead to BIR-mediated translocation events.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the cohesion defect impairs sister chromatid recombination [31,66], increasing intra-chromatid recombination in the tandem array of ribosomal repeats [36]. Recent work even suggested that Smc5-Smc6 would be required for the efficient loading of cohesin to DSB sites [67,68]. Smc5-Smc6 could restrain the initiation of strand invasions between different chromosomes that lead to BIR-mediated translocation events.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in genes involved in the SUMO pathway, such as Ubc9, Mms21, Ulp1, Slx5 and Slx8, render cells sensitive to DNA damage, and many proteins involved in the maintenance of genome stability have been shown to become sumoylated during the damage response [23][24][25][26][27][28]. Specifically, it has been shown that the SUMO pathway plays an important role in homologous recombination and the resumption of stalled/collapsed replication forks [27,[36][37][38].…”
Section: Dna Repair and Sumo In Yeastmentioning
confidence: 99%
“…This complex is specifically required for recombination between sister chromatids in both yeast [37] and man [36], and is recruited to DSBs in G2/M cells [37,42]. Moreover, it contributes to the maintenance of telomeric repeats by recombination in telomerasedeficient cells [21].…”
Section: Dna Repair and Sumo In Yeastmentioning
confidence: 99%
See 1 more Smart Citation
“…Since APRIN appeared to modulate HR capacity, we investigated whether APRIN was localised at the site of a DSB. To assess this, we designed a chromatin IP (ChIP) assay based upon the HR reporter described in Figure 4C and similar to that previously described by Potts and colleagues (Potts et al, 2006). Cells harbouring a genomic DR-GFP reporter were transfected with an I-SceI expression construct that caused a DSB within the reporter construct.…”
Section: Aprin Is Required For Efficient Dna Repairmentioning
confidence: 99%